The rocky road travelled by the Dutch Reformed Church in Africa towards church unity: from Tshilidzini to Pretoria, 1971 to 1991 - Modise, Leepo (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
This review of the rocky road travelled by the Dutch Reformed Church in Africa (DRCA) towards church unity consists of five parts. First, the historical background to the DRCA is briefly traced. Second, the author investigates the various decisions of the general synod of the DRCA regarding church unification from Tshilidzini in 1971 to Pretoria in 1991. Third, decisions of the general synod of the then DRCA on the fourth confession are considered. Fourth, the decision of the general synod regarding the Belhar confession prior to 14 April 1994 and the unity talks among the then Dutch Reformed Church (DRC) members and their impact on unity are discussed. Fifth, the final decisions of the then DrcA regarding church unification with the Dutch Reformed Mission Church (DRMC) as the result of the delay on the part of the DRC are investigated.